2007
DOI: 10.1177/112067210701700312
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Deep Scleral Flap Size on Intraocular Pressure after Deep Sclerectomy

Abstract: Greater weight, surface area, and volume of the deep scleral flap dissected during deep sclerectomy achieve significantly lower postoperative IOPs in the early postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…16 Those preliminary results suggest that, at least in the early postoperative period, the mean postoperative IOP could be an indicator of adequate inner scleral flap dissection.…”
Section: Discussionmentioning
confidence: 95%
“…16 Those preliminary results suggest that, at least in the early postoperative period, the mean postoperative IOP could be an indicator of adequate inner scleral flap dissection.…”
Section: Discussionmentioning
confidence: 95%
“…This difference, which was not found in other reports that compared nonpenetrating surgery with penetrating surgery [1,[16][17][18] could be explained by differences in the trabeculectomy technique because, unlike the other studies, in the current study we did not enlarge the communication beyond the TDM, and excised a deep scleral block smaller than that in classic trabeculectomy. It had been reported that an increase in the weight and size of the deep scleral flap might result in a greater IOP reduction [19]. The fact that conjunctival and scleral flaps are smaller in standard trabeculectomy than in non-penetrating surgery converted to trabeculectomy could contribute in increasing the risk of scarring and failure of the latter, as there is a greater wound surface.…”
Section: Discussionmentioning
confidence: 97%